2019
DOI: 10.1111/vec.12817
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high flow nasal cannula oxygen administration to traditional nasal cannula oxygen therapy in healthy dogs

Abstract: Objective:To determine the feasibility, degree of respiratory support, and safety of high flow nasal cannula (HFNC) oxygen therapy in sedated and awake healthy dogs, when compared to traditional nasal cannula (TNC) oxygen administration.Design: Randomized experimental crossover study.Setting: University research facility. Animals: Eight healthy dogs.Interventions: Variable flow rates (L/kg/min) were assessed, TNC: 0.1, 0.2, and 0.4 and HFNC: 0.4, 1.0, 2.0, and 2.5. HFNC was assessed in sedated and awake dogs.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(80 citation statements)
references
References 25 publications
(61 reference statements)
2
63
0
4
Order By: Relevance
“…() and Jagodich et al . () in healthy dogs and Keir et al . () in hypoxaemic dogs also showed this PaO 2 improvement after HOT.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…() and Jagodich et al . () in healthy dogs and Keir et al . () in hypoxaemic dogs also showed this PaO 2 improvement after HOT.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, a recent study with the same system showed that, when delivering a FIO 2 of 100%, the effective delivered FIO 2 increases with flow rate and varies between 72.2 and 95% for flow rate from 0.4 to 2.5 L/kg/minute (Jagodich et al . ). In our study, flow rate ranged from 0.44 to 1.84 L/kg/minute, so we think it probable that the effective FIO 2 did not reach 100%.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations